Verifikasi Dosis Radiasi Permukaan pada Kasus Kanker Payudara Menggunakan Metode Dosimetri In Vivo - Sri Wulandari; Rico Adrial; Syarifatul Ulya; Fiqi Diyona (Jurnal Fisika Unand, 2024)
Verification of surface radiation dose in breast cancer cases using the in vivo dosimetry method with TLD-100 at the Radiation Oncology Unit of Andalas University Hospital has been carried out. The aim of the study is to verify the adequacy of the surface radiation dose calculated by the Treatment Planning System (TPS) with the measured radiation dose of TLD-100, referring to the report of the American Association of Physicists in Medicine Task Group No.219 (AAPM-TG No.219). This study began with the annealing of the TLD-100, namely the cleaning of the electrons trapped by the TLD-100 at the Research Center for Safety Technology Metrology and Nuclear Quality of the National Innovation Research Agency (PRTKMMR-BRIN), followed by the scanning of the TLD-100 on the surface of the phantom plate using a CT simulator. In addition, the TLD-100 was calibrated with different radiation doses (0; 20; 50; 80; 100; 150; 200; 250; 370) cGy. Verification of surface radiation dose on five breast cancer treatment planning data with TPS surface radiation dose calculation by Patient Specific Quality Assurance (PSQA) or transfer of patient treatment plan to slab phantom and compared with radiation dose measured on TLD 100. The measured surface radiation dose was found to range from 115.07 cGy to 130.81 cGy. Verification showed that the difference between the radiation dose calculated by the TPS and that measured by the TLD-100 was 0.21% to 8.13%. This shows that the surface radiation dose in breast cancer cases is within the 20% tolerance limit set by AAPM-TG No.219.